'Irish … but nothing Irish': The performance of Ireland on the British colonial stage. Issue 1 (1st December 2020) - Gannon, Seán William
In a perceptive essay on Scottish national and imperial identity, Richard J. Finlay framed what he termed the 'transplantation of "Highlandism"' to the colonies through Scottish societies, Highland dancing clubs and Burns nights as the 'performance of Scotland' overseas. Using a range of documentary archival sources and written and oral personal testimonies, this essay applies Finlay's idea to Irish communalization in the twentieth-century British dependent empire. The transient 'imperial Irish' diasporas that Irish soldiers, settlers, colonial servants and missionaries comprised formed an integral and generally indiscernible part of the British ruling class. However, Irishness was spatialized in colonial life through Irish clubs, societies and St Patrick's Day celebrations which enacted a 'stage' performance of Ireland based on ritualized caricature and trope. This performance was also thoroughly imperialized and was directed with performative purpose. It worked to ecumenize the social, religious and political 'varieties of Irishness' that co-existed in British colonial life; 'imperial Irish' diasporas represented the heterogeneity of twentieth-century Irish identities and these performances created depoliticized spaces which emphasized commonalities rather than contrasts. Inter-accommodation of these disconsonant identities was required in the colonies where 'British' ethnic, political and religious differences had to be submerged to preserve the more critical distinction between colonizer and colonized on which the empire's legitimacy and sustainability depended. The colonial performance of Ireland also served to demonstrate that Irishness and loyalty to the Crown and empire were not, by definition, dichotomous: the non-threatening, imperialized image of Irishness that they presented countered the enduring trope of the Irish as 'natural subversives'.